Inverse optimization for multi-objective linear programming - Naghavi, Mostafa; Foroughi, Ali Asghar; Zarepisheh, Masoud (Optimization letters, 2019)
This paper generalizes inverse optimization for multi-objective linear programming where we are looking for the least problem modifications to make a given feasible solution a weak efficient solution. This is a natural extension of inverse optimization for single-objective linear programming with regular “optimality” replaced by the “Pareto optimality”. This extension, however, leads to a non-convex optimization problem. We prove some special characteristics of the problem, allowing us to solve the non-convex problem by solving a series of convex problems.